Organizational Justice and Workplace Deviance: The Mediating Role of Job Satisfaction - Subedi, Rita; Lama, Padam Bahadur; Dhakal, Anisha; Shrestha, Lasata (Nepalese Journal of Business and Management Studies, 2024)
The purpose of this study was to investigate how organizational justice comprising procedural, distributive, and interactional justice influences on workplace deviance through job satisfaction among employees working in academic institutions in the Sorhakhutte , Kathmandu. Thus, this research employed descriptive and causal research designs to reflect the general background of survey participants and to test the formulated research hypotheses of the study. Further, the structured questionnaires utilized in the study for cross-sectional primary sources of Therefore, this study used 106 useful data for the analysis. Descriptive statistics and regression analysis were used to evaluate the study hypotheses. The findings demonstrate a substantial adverse effect of organizational justice and job satisfaction on workplace misbehavior. Furthermore, organizational justice has a beneficial impact on work satisfaction. Job satisfaction partly mediates the association between distributive justice, procedural justice, and workplace deviance, underscoring the significance of equity and support in alleviating deviant behavior. Job satisfaction does not serve as a mediator in the link between interactional justice and workplace misbehavior. These results underscore the essential function of management in fostering equity and justice to improve job satisfaction and mitigate workplace deviance.